Designing The Proposed Improvement of TIX ID Online Cinema Ticket Purchase Service Quality - Julya Ditazha; Eko Pujiyanto; I Wayan Suletra (Jurnal Ilmiah Teknik Industri, 2020)
TIX ID is application in Indonesia that provides new experiences in purchasing cinema tickets. The success of a company can be seen from service quality in fulfilling the satisfaction of customers. Therefore, the purpose of this study is to designing the proposed improvement TIX ID online cinema ticket purchase service quality. This study was conducted in three stages, namely testing the hypotheses of the relationship between variables using PLS-SEM, measuring service quality using the servqual method, and designing the proposed improvement. The result of this study is e-service quality has a significant effect on e-satisfaction and e-loyalty. In addition, the dimensions of e-service quality are dominant effect on the low TIX ID service quality is compensation, with a gap of 27%. Recommendations for improvement are providing customer access to be able to contact customers service directly and SOP of the cooperation TIX ID and DANA.